Method for extracting iron by settling copper slag and application of method
By mixing copper slag with calcium oxide-based additives, heating and reconstructing ore phases, and crystallization and sedimentation under insulation conditions, the problems of long process flow and many impurities in the existing copper slag iron extraction technology are solved, and efficient and economical iron resource recovery is achieved.
Patent Information
- Application Number
- CN202411695876.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-07
AI Technical Summary
The existing copper slag iron extraction technology has a long process flow, resulting in high recycling costs, and there are a large number of impurities in the recovered iron, which makes it difficult to use later.
By mixing the copper slag with calcium oxide-based additives, heating and reconstructing the ore phase to form the modified copper slag, crystallization and precipitation under insulation conditions, and the iron concentrate is collected.
It realizes efficient recycling of iron resources in copper slag, simplifies the process, reduces energy consumption and pollution, and improves iron recovery and product purity.
Smart Images

Figure CN119571050A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of copper slag solid waste treatment, and specifically relates to a method for extracting iron by settling copper slag and application thereof. Background Art
[0002] In the copper production process, an average of 2.2 tons of copper slag is produced for every ton of copper produced. Copper slag is difficult to dispose of, and the accumulated copper slag over the years is conservatively estimated to have exceeded 100 million tons, occupying a large amount of land resources, causing serious secondary pollution of heavy metals and waste of resources. In fact, copper slag is rich in iron, so it is crucial to properly treat copper slag and fully utilize the iron resources in copper slag.
[0003] At present, the commonly used technology for extracting iron from copper slag is to reduce the copper slag into metallic iron phase through reduction. However, there are problems such as long process flow resulting in high recovery cost, large amount of impurities in the recovered iron, and difficulty in subsequent utilization. Summary of the invention
[0004] The invention aims to solve the technical problems in the above-mentioned conventional technology of extracting iron from copper slag, such as long process flow leading to high recovery cost, large amount of impurities in the recovered iron, and difficulty in subsequent utilization. The present invention provides a method for extracting iron from copper slag by sedimentation, comprising the steps of:
[0005] Mixing copper slag and a calcium oxide-based additive to obtain a mixed copper slag, wherein the calcium oxide-based additive includes calcium oxide and / or the calcium oxide raw material, the calcium oxide raw material can generate calcium oxide by heating, and the amount of the calcium oxide-based additive added satisfies that the total mass of the native calcium oxide and / or the generated calcium oxide is 29% to 47% of the mass of the fayalite phase in the copper slag;
[0006] The mixed copper slag is heated to 1200° C. to 1800° C. to reconstruct the mineral phase, thereby obtaining modified copper slag; the main components of the modified copper slag include magnetite and β-type dicalcium silicate;
[0007] The modified copper slag is crystallized and settled for 10 to 20 hours under the insulation condition of 1400 to 1800° C., and the mother liquor is collected to obtain the iron concentrate.
[0008] Furthermore, the calcium oxide raw material includes calcium carbonate and / or calcium sulfate.
[0009] Furthermore, in the case where the calcium oxide-based additive is the calcium oxide raw material, the temperature at which the mixed copper slag undergoes the mineral phase reconstruction is 1200-1800°C.
[0010] Furthermore, in the case where the calcium oxide-based additive is calcium oxide, the temperature at which the mixed copper slag undergoes the mineral phase reconstruction is 1400-1800°C.
[0011] Furthermore, in the case where there is no crystal-stabilizing ion with a mass proportion greater than 0.5% in the copper slag, crystal-stabilizing ions are added to the copper slag until the mass proportion of the crystal-stabilizing ions in the copper slag reaches more than 0.5%, and the ionic polarization ability of the crystal-stabilizing ions is less than 4 or greater than 39.
[0012] Further, the crystal stabilizing ions include Na + , K+, Ba 2+ , Sr 2+ , Mn 6+ 、V 5+ Cr 6+ , P 6+ One or more of .
[0013] Furthermore, in terms of mass fraction, the content of the fayalite phase in the copper slag is 10% to 40%.
[0014] Furthermore, in the step of collecting the mother liquor after the modified copper slag is crystallized and settled for 10 to 20 hours under heat preservation conditions, the product after the modified copper slag is crystallized and settled includes upper particles and the mother liquor, and the upper particles are β-type dicalcium silicate.
[0015] Furthermore, the mass percentage of Fe3O4 in the iron concentrate is more than 92%.
[0016] The present invention also provides an application of the method for extracting iron by settling copper slag as described in any one of the above items in copper slag treatment.
[0017] Compared with the prior art, the present invention has at least the following advantages:
[0018] like Figure 2 As shown, the present invention provides a method for extracting iron from copper slag by settling, wherein a calcium oxide additive is added to the copper slag, and the calcium content in the calcium oxide additive is limited to 29% to 47% of the mass of the fayalite phase in the copper slag, and the composition point of the copper slag is precisely controlled in the C2S primary crystallization zone in the CaO-FeO-SiO2 phase diagram, so that the iron content of the liquidus is more than 90%, and the temperature setting of the ore phase reconstruction is coordinated to enrich the iron element in the liquid phase, thereby achieving a significant increase in the recovery rate of iron resources in the copper slag from the source.
[0019] Based on the composition of the modified copper slag after mineral phase reconstruction (main components include magnetite and β-type dicalcium silicate), the present invention can purify and recover the magnetite in the copper slag through crystallization and sedimentation, thereby simplifying the process and effectively avoiding the energy consumption and mineral processing pollution in the crushing and grinding processes in the commonly used technologies. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0021] Figure 1 It is a schematic diagram of a flow chart in one embodiment of the present invention;
[0022] Figure 2 1 is a CaO-FeO-SiO2 ternary phase diagram used in one embodiment of the present invention.
[0023] Figure 3 FIG. 1 is a schematic diagram of forming a dense C2S shell layer when the calcium oxide-based additive is calcium oxide in one embodiment of the present invention. DETAILED DESCRIPTION
[0024] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0026] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.
[0027] The present invention provides a method for extracting iron by settling copper slag, comprising the steps of:
[0028] S1. Mixing copper slag and a calcium oxide-based additive to obtain a mixed copper slag, wherein the calcium oxide-based additive includes calcium oxide and / or the calcium oxide raw material, the calcium oxide raw material can generate calcium oxide by heating, and the amount of the calcium oxide-based additive added satisfies: the total mass of the native calcium oxide and / or the generated calcium oxide is 29% to 47% of the mass of the fayalite in the copper slag.
[0029] The native calcium oxide is the calcium oxide included in the calcium oxide-based additive, and the generated calcium oxide is the calcium oxide that can be generated by heating the calcium oxide raw material.
[0030] Herein, heating generation refers to that the calcium oxide raw material is heated to a certain temperature to release carbon dioxide and / or sulfur dioxide to generate calcium oxide.
[0031] Exemplarily, the total mass of native calcium oxide and / or generated calcium oxide can be 29% to 47% of the mass of fayalite in copper slag, such as 30% to 35%, 40% to 43%; in some specific embodiments, the total mass of native calcium oxide and / or generated calcium oxide can be 29% to 30% of the mass of fayalite in copper slag; in some more specific embodiments, the total mass of native calcium oxide and / or generated calcium oxide can be 40% to 41% of the mass of fayalite in copper slag.
[0032] In some embodiments, the copper slag may be copper smelting slag or copper tailings slag.
[0033] In common technologies, the composition points of copper slag after adjustment are mostly concentrated in the primary crystal region of FeO in the CaO-FeO-SiO2 phase diagram, such as Figure 2 As shown in area ① in the figure, the liquidus content of iron in the primary crystal area is relatively low, and most of the iron will still precipitate in the form of pyroxene together with calcium, silicon and oxygen, reducing the iron recovery rate.
[0034] In comparison, the present invention controls the composition point in the copper slag in the C2S primary crystallization zone in the CaO-FeO-SiO2 phase diagram by adjusting the amount of calcium oxide-based additives added, so that the liquidus iron content reaches more than 90%, and the iron element is enriched in the mother liquor, which step-wise optimizes the recovery effect of the iron element and minimizes iron loss.
[0035] Calcium oxide-based additives include calcium carbonate, calcium sulfate and / or calcium oxide.
[0036] In some embodiments, when there is no crystal-stabilizing ion with a mass percentage greater than 0.5% in the copper slag, crystal-stabilizing ions are added to the copper slag until the mass percentage of the crystal-stabilizing ions in the copper slag reaches more than 0.5%, and the ionic polarization ability of the crystal-stabilizing ions is less than 4 or greater than 39.
[0037] The ion polarizability is the attraction or repulsion of the electric field generated by a charged ion on the electron cloud of another ion, which can be expressed as C 2 / R represents (C – charge, R – ionic radius).
[0038] Exemplary, the crystal stabilizing ions may include Na + , K+, Ba 2+ , Sr 2+ , Mn 6+ 、V 5+ Cr 6+ , P 6+ One or more of .
[0039] As another example, the crystal stabilizing ion can be added in the form of a crystal stabilizer, and the crystal stabilizer includes Ca3(PO4)2.
[0040] In some embodiments, the added mass of Ca3(PO4)2, after being calculated as the added amount of P element, can be 0.5% to 2.0% of the mass of the copper slag.
[0041] Exemplarily, the added mass of Ca3(PO4)2 may be 5% of the mass of the copper slag.
[0042] The addition of crystal stabilizer can inhibit the solid phase transition of β-C2S→γ-C2S during the subsequent temperature drop. β-C2S has gelling properties and is an important component of cement clinker, which has an important influence on the strength and other properties of cement. The β-dicalcium silicate obtained by subsequent sedimentation can be used as the main component of cement clinker and enter the cement industry, realizing the full quantitative utilization of copper slag.
[0043] S2. The mixed copper slag is heated to 1200° C. to 1800° C. to reconstruct the mineral phase, thereby obtaining modified copper slag; the main components of the modified copper slag include magnetite and β-type dicalcium silicate.
[0044] Based on the total mass of the native calcium oxide and / or the generated calcium oxide in step S1, the composition point of the mixed copper slag of the present invention is located at Figure 2 The applicant found that if Figure 3 As shown, the mixed copper slag of this composition will form a dense high-melting-point dicalcium silicate shell during the mineral phase reconstruction process, which will cover the surface of calcium oxide and inhibit the reaction process of calcium oxide (calcium oxide can react with silicon dioxide in the slag, effectively destroying the fayalite phase, reducing fayalite formation, and promoting the transformation of the fayalite phase in the slag).
[0045] In view of this, when the calcium oxide-based additive is calcium oxide, the temperature of mineral phase reconstruction can be 1400-1800°C. The dicalcium silicate shell melts at this temperature, which ensures that calcium oxide and silicon dioxide react fully and provides the necessary energy and kinetic conditions for the subsequent precipitation and crystallization of β-dicalcium silicate.
[0046] When the calcium oxide additive is a calcium oxide raw material, the temperature of the mineral phase reconstruction can be relaxed to 1200-1800°C, such as 1200-1400°C, because:
[0047] CaCO3→CaO+CO2 (the CO2 produced by the reaction can break the dense C2S shell and reduce the reaction temperature, otherwise the shell needs to be dissolved by heating)
[0048] CaSO4→CaO+SO2 (SO2 produced by the reaction can break up the dense C2S shell and reduce the reaction temperature, otherwise the shell needs to be dissolved by increasing the temperature)
[0049] Calcium carbonate and calcium sulfate decompose endothermically under high temperature conditions, and the generated carbon dioxide or sulfur dioxide gas can destroy the dicalcium silicate shell, fully exposing calcium oxide, and allowing the reaction between calcium oxide and silicon dioxide to proceed. The present invention achieves stable optimization of iron recovery rate by synergistically adjusting the type of calcium oxide-based additives and the temperature of mineral phase reconstruction. In comparison, in conventional technologies, only monocalcium silicate will be generated in the copper slag that falls into the FeO primary crystallization zone. The density of monocalcium silicate does not meet the standard of blocking the reaction kinetics, so it will not form a dense shell, and will not face the technical problem of dicalcium silicate shell coating in this application, and there is no motivation to adjust the type of calcium oxide-based additives and the temperature of mineral phase reconstruction.
[0050] S3. After the modified copper slag is crystallized and settled for 10 to 20 hours under the insulation condition of 1400 to 1800° C., the mother liquor, i.e., the iron concentrate, is collected.
[0051] Recovering iron from copper slag through crystallization and sedimentation avoids energy consumption in subsequent crushing and grinding processes and pollution in the mineral processing process, significantly reduces costs and increases efficiency, and has excellent economic and environmental benefits.
[0052] In the commonly used technology, the slag after slow cooling needs to be crushed and ground into a reduction product with a particle size of more than 200 meshes. The production line is long and the production cost is high.
[0053] On the one hand, during the slow cooling process, the components in the slag are unlikely to have enough time to diffuse and rearrange, making it difficult to form larger crystal particles. If a mineral processing process is required, the particle size must be ground to a very fine size, which increases the grinding cost. Coupled with the requirement for grinding products above 200 mesh, the energy consumption and equipment loss can be imagined. It should also be noted that more than 90% of the energy consumed in the grinding process will be dissipated in the form of heat energy. From the perspective of energy utilization, grinding itself is a very cost-effective means.
[0054] On the other hand, the grinding products of this particle size grade have tiny particle size and high specific surface area, which are easy to stick to the screening equipment or the surface of the grinding medium during the grinding process, resulting in product loss.
[0055] In some specific embodiments, when the temperature of mineral phase reconstruction is not higher than 1400°C, such as 1200°C to 1400°C, the temperature can be raised to 1400°C and then kept at this temperature for crystallization and sedimentation.
[0056] The products after crystallization and sedimentation of the modified copper slag include upper particles and the mother liquor, and the upper particles are β-type dicalcium silicate.
[0057] For example, Figure 1 As shown, the upper particles and the mother liquor can be separated by layered discharge.
[0058] It should be noted that the solid phase transition trend of β-C2S→γ-C2S is enhanced during the cooling process at around 725°C.
[0059] β-Dicalcium silicate can enter the cement industry as the main component of cement clinker, realizing the full quantitative utilization of copper slag.
[0060] The mass proportion of Fe3O4 in the iron concentrate is more than 92%. After conversion, the iron grade is more than 65%, which meets the conditions for entering the pre-iron system (such as sintering or pelletizing). The iron concentrate can enter the pre-iron system to further recover iron products.
[0061] In order to facilitate those skilled in the art to further understand the present invention, examples are given below:
[0062] Example 1
[0063] The copper slag is copper smelting slag. Chemical phase analysis of the copper slag shows that the mass content of fayalite is 15.5%, the mass content of magnetite is 20.7%, and the total iron content is 39.6%.
[0064] Copper slag carries C2S crystal stabilizing ions Na +, the content is 1.46%, and a CaO-based additive is added to the copper slag to obtain a mixed copper slag; the calcium oxide-based additive is CaCO3, and the addition amount of CaCO3 is 11% of the mass of the copper slag, that is, the calcium oxide content in the calcium oxide-based additive is 39.7% of the mass of the fayalite phase;
[0065] The mixed copper slag is heated to 1700°C for mineral phase reconstruction to obtain modified copper slag, the main components of which are magnetite and β-C2S.
[0066] The modified copper slag was kept at 1700℃ for crystallization and sedimentation, and the sedimentation time was 12h.
[0067] The products after sedimentation are discharged in layers. After sedimentation, the upper particles are β-C2S, and the lower liquid is iron concentrate. The Fe3O4 content in the iron concentrate is more than 92%, the iron recovery rate is more than 90%, and the iron grade of the obtained magnetite is more than 65%, which is qualified to enter the pre-iron system. The upper particles can be collected and used as raw materials for the cement industry.
[0068] Example 2
[0069] The copper slag is copper tailings slag. Chemical phase analysis of the copper slag shows that the mass content of fayalite is 17.64%, the mass content of magnetite is 23.87%, and the total iron content is 45.8%.
[0070] There is no crystal stabilizing ion with a mass concentration greater than 1% in the copper slag, so a crystal stabilizer Ca3(PO4)2 is added to the copper slag in an amount of 3% of the mass of the copper slag to stabilize the crystal stabilizing ions P in the copper slag. 6+ The concentration is adjusted to 0.6%. Then, a CaO-based additive is added to the copper slag to obtain a mixed copper slag; the calcium oxide-based additive is CaO, and the amount of CaO added is 6% of the mass of the copper slag, that is, the calcium oxide content in the calcium oxide additive is 34.0% of the mass of the fayalite;
[0071] The mixed copper slag is heated to 1800°C to reconstruct the mineral phase to obtain the modified copper slag, the main components of which are magnetite and β-C2S.
[0072] The modified copper slag was kept at 1700℃ for crystallization and sedimentation, and the sedimentation time was 15h.
[0073] The products after sedimentation are discharged in layers. After sedimentation, the upper particles are β-C2S, and the lower liquid is iron concentrate. The Fe3O4 content in the iron concentrate is more than 95%, which is qualified to enter the pre-iron system. The upper particles can be collected and used as raw materials for the cement industry.
[0074] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for extracting iron from copper slag by sedimentation, characterized in that: Includes steps: Mixing copper slag and a calcium oxide-based additive to obtain a mixed copper slag, wherein the calcium oxide-based additive includes calcium oxide and / or the calcium oxide raw material, the calcium oxide raw material can generate calcium oxide by heating, and the amount of the calcium oxide-based additive added satisfies that the total mass of the native calcium oxide and / or the generated calcium oxide is 29% to 47% of the mass of the fayalite phase in the copper slag; The mixed copper slag is heated to 1200° C. to 1800° C. to reconstruct the mineral phase, thereby obtaining modified copper slag; the main components of the modified copper slag include magnetite and β-type dicalcium silicate; The modified copper slag is crystallized and settled for 10 to 20 hours under the insulation condition of 1400 to 1800° C., and the mother liquor is collected to obtain the iron concentrate.
2. The method for extracting iron by copper slag sedimentation according to claim 1, characterized in that: The calcium oxide raw material includes calcium carbonate and / or calcium sulfate.
3. The method for extracting iron by copper slag sedimentation according to claim 2, characterized in that: In the case where the calcium oxide-based additive is the calcium oxide raw material, the temperature at which the mixed copper slag undergoes the mineral phase reconstruction is 1200-1800°C.
4. The method for extracting iron by copper slag sedimentation according to claim 1, characterized in that: In the case where the calcium oxide-based additive is calcium oxide, the temperature at which the mixed copper slag undergoes the mineral phase reconstruction is 1400-1800°C.
5. The method for extracting iron by copper slag sedimentation according to claim 1, characterized in that: In the case where there is no crystal-stabilizing ion with a mass proportion greater than 0.5% in the copper slag, crystal-stabilizing ions are added to the copper slag until the mass proportion of the crystal-stabilizing ions in the copper slag reaches more than 0.5%, and the ion polarization ability of the crystal-stabilizing ions is less than 4 or greater than 39.
6. The method for extracting iron by copper slag sedimentation according to claim 5, characterized in that: The crystal stabilizing ions include Na + , K+, Ba 2+ , Sr 2+ , Mn 6+ 、V 5+ Cr 6+ , P 6+ One or more of .
7. The method for extracting iron by settling copper slag according to claim 1, characterized in that: Calculated by mass fraction, the content of the fayalite phase in the copper slag accounts for 10% to 40%.
8. The method for extracting iron by copper slag sedimentation according to claim 1, characterized in that: After the modified copper slag is crystallized and settled for 10 to 20 hours under heat preservation conditions, in the step of collecting the mother liquor, the product after the modified copper slag is crystallized and settled includes upper particles and the mother liquor, and the upper particles are β-type dicalcium silicate.
9. The method for extracting iron by copper slag sedimentation according to claim 1, characterized in that: The mass percentage of Fe3O4 in the iron concentrate is more than 92%.
10. Use of the method for extracting iron by settling copper slag as claimed in any one of claims 1 to 9 in copper slag treatment.
Citation Information
Cited By
Method for efficiently extracting iron from copper slag through non-molten hydrogen reduction
CN121109739A
Method for inhibiting generation of liquid phase in fayalite type slag reduction roasting product
CN121992188A